Enhanced green fluorescent protein-transfection of murine colon carcinoma cells: key for early tumor detection and quantification - Sturm, Jörg; Keese, Michael; Petruch, Beate; Bönninghoff, Roderich; Zhang, Honyue; Gretz, Norbert; Hafner, Mattias; Post, Stefan; Mc Cuskey, Robert S. (Clinical & experimental metastasis, 2003)
Many animal models for metastatic colorectal cancer represent clinical manifestations just inaccurately. We introduce a novel mouse model for metastastatic colorectal cancer. In order to remain close to the clinical disease a syngenic murine colon carcinoma cell line (colon 26 cells) was transfected with enhanced green fluorescent protein (EGFP). The transfected cells maintain the highly malignant attributes of the wild-type cells. Following injection into the portal circulation of Balb/c-mice, liver metastases occur in the same time span. Using the fluorescent attributes of the transfected cells, an approximation of the tumor load in liver tissue can be achieved by fluorescence activated cell sorting (FACS) and fluoroscan analysis. Tumor cell load in liver tissue can be accurately measured by Northern blot and Western blot analysis of liver tissue containing EGFP-transfected colon cancer metastases (1250 cells/mg liver tissue and 1000 cells/mg liver tissue) respectively. Confocal microscopy and intravital microscopy confirmed the growth of tumor metastases, originating from the intravascular compartments. The presented animal model using EGFP-transfected colon 26 cells allows the detecting of tumor growth in vivo and post mortem, as well as an accurate quantification of the tumor load in the liver tissue.
Gesehen am 22.06.2022